Assessment of the Possibilities of Forensic Identification Population of Kazakhstan by Craniometric Indicators - Mussabekova, Saule; Stoyan, Anastassiya; Mkhitaryan, Xeniya (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Craniometric indicators are one of the most reliable sources of information about the population. Despite the development of genetic methods, skull measurements are extremely important in anthropology and forensic medicine. In addition to the history of population development, environmental factors such as climate and lifestyle contribute to variations in human skull shape. Due to the high variability of human individuals, the anthropological study of the population is carried out selectively, with a comparison of different population groups (ethnic, professional, age, gender). The lack of clear ideas about the typical parameters and proportions of the skull among the people of Kazakhstan creates a certain gap in forensic-medical identification. AIM: The aim of the work is to check the hypothesis about the relationship between variations in skull morphology and changes in craniometric indicators with climatic conditions and the specifics of lifestyle in populations living in different territories of Kazakhstan. METHODS: 187 male and 114 female adult skulls found on the territory of the two largest regions of Kazakhstan were examined. The variable variability of 25 craniometric indicators of skulls found on the territory of Central and South Kazakhstan was studied. All osteometric changes were performed using standard anthropometric instruments, followed by the calculation of craniometric indices. Multidimensional statistics were applied. RESULTS: The two populations demonstrate differences in craniometric indicators formed in different geographical and ecological conditions, regardless of gender. It was found that the sizes of the skulls found in the two studied regions of Kazakhstan statistically significantly differ in 5 craniometric indicators for men and 8 craniometric indicators for women. Significant changes were noted in the size of the full and upper height of the face, the average width of the face, the height of the body of the lower jaw and the height of the nose in men. The most dimorphic variables for forensic medical evaluation in the studied populations of female skulls were transverse, altitudinal and zygomatic diameters, mastoid width, width of the base of the skull, width of the occipital foramen, upper face height and nose height. The shape of the skulls found in the studied territories is predominantly brachycephalic. The cranial index was >81.1% - at men, 83% - at women. The study showed that race affects the size of the skull, regardless of gender. Craniometric parameters in male and female skulls vary according to different criteria. In women between races, there are statistically significant differences in the size of the width of the occipital foramen and the average width of the face. Statistically significant differences in the width of the base of the skull, the zygomatic diameter and the average width of the face between the Caucasoid and Mongoloid races were revealed in the studied regions in men. The established differences made it possible to form additional differential diagnostic criteria. CONCLUSION: Identification of the features inherent in the population living in certain territories provides auxiliary information for medical and forensic identification of a person. In this study, population-specific craniometric indicators have been developed for inhabitants of two regions of Kazakhstan, which expand and complement identification capabilities when categorizing skeletal remains found in these territories.